International knowledge transfer in religious education: universal validity or regional practices? Backgrounds, considerations and open questions concerning a new debate - Schweitzer, Friedrich (British Journal of religious education, 2020)
This article refers to the new European discussion on international knowledge transfer in religious education. Readers are introduced to the background of the recent manifesto ‘International Knowledge Transfer in Religious Education: A Manifesto for Discussion’ which was the outcome of a first international consultation of researchers in the field of religious education in October 2018. In a first step, the demand for international knowledge transfer in religious education is described. Furthermore, the question of the validity of knowledge in religious education is taken up and discussed in the sense of the presuppositions of international transfer and cooperation. Special attention is given to the relationship between universal and contextual elements or dimensions of knowledge in religious education and their epistemological implications which the authors consider a general and fruitful challenge for the discipline, in international as well as in national contexts. In conclusion, the authors set forth a number of perspectives for future research concerning international knowledge transfer in religious education.